The Socio-Economic Effects of Medical Unions Strikes on the Health Sector of Akwa Ibom State of Nigeria - Essien, Madara Joseph (Asian Business Review, 2018)
This study was a cross-sectional descriptive survey conducted with the general objective to describe the socioeconomic effects of medical union strikes on Nigeria’s health sector, with particular focus on Akwa Ibom State. Four research questions were formulated that guided the study. Data were collected from respondents who constituted staff, medical students and patients of Akwa Ibom State public hospitals. These formed the population of the study while 150 individuals were randomly selected as sample size. Double sampling technique was adopted while simple random sampling method was used to achieve the purpose of adopting it. The instruments used for data collection was survey questionnaire and oral interview with a tape recorder. The criterion-related validity and test-re-test reliability were methods adopted to test for the validity and reliability of research instruments. The data collected were analyzed using descriptive analytics techniques such as frequency distribution, measures of central tendency, percentages and measures of dispersion. From the analysis, it was revealed that the incessant health workers strikes are fundamentally caused by poor remuneration, denial to salary review and non-payment of accrued salaries. It was also seen that negative socioeconomic effects of which the major ones included avoidable deaths, poor health complications and disease spread outweighed the positive socioeconomic effects which were salary review, payment of accrued wages, provision of medical equipment and improved welfare of health workers. This was viewed in terms of their impacts on the economic indices of the nation. The study recommends among other things that government should pay health workers salaries regularly and improved infrastructure of health centres to enhance service delivery. On the other hand, workers should make demands that are moderate and not beyond the capacity of their employers and should provide certain essential services while on strike.